Bmi-1 induces radioresistance in MCF-7 mammary carcinoma cells - LIU, ZHI-GANG (D.A. Spandidos, 2011)
Bmi-1, a member of the polycomb family, it is involved in self renewal of stem cells and functions as an oncogene in many malignant human cancer types. Recent studies have demonstrated that Bmi-1 is a predictive factor for poor patient prognosis. However, the underlying mechanisms of radioresistance mediated by Bmi-1 are poorly understood. In this study, the dose-survival relationship was analyzed using a clonogenic survival assay and combined radiation treatment with Bmi-1 overexpression or silencing. DNA double-strand break (DSB) and repair was assessed by immunofluorescence staining of γH2AX foci. In addition, mitochondrial membrane potential was detected between Bmi-1 knockdown and control MCF-7 cells after irradiation. Apoptosis and cell cycle were evaluated by flow cytometry. We found that exposure of MCF-7 cells overexpressing Bmi-1 to ionizing radiation resulted in dramatically enhanced survival relative to control cells, whereas cells with silenced Bmi-1 showed markedly reduced survival. Bmi-1 inhibition significantly increased DSBs and decreased DSB repair. Furthermore, Bmi-1 knockdown induced loss of mitochondrial membrane potential and enhanced apoptosis by up-regulating p53, p21, Bax expression and down-regulating p-AKT and Bcl-2 expression. These results indicate that Bmi-1 may play an important role in radiosensitivity, and the suppression of its expression might be a potential therapeutic target for breast cancer.